PENGARUH MODEL PBL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI PIKTOGRAM DAN DIAGRAM BATANG - Nurfitriyani, Dini; Irawati, Riana; Gustian Nugraha, Rana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low mathematical problem-solving ability of students in the topics of pictograms and bar charts. Students still experienced difficulties in interpreting data and solving problems; therefore, a learning model that can enhance these abilities is needed. This study aims to determine the effect of the Problem-Based Learning (PBL) model on students’ mathematical problem-solving skills. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The sample was selected using a purposive sampling technique, resulting in SDN Malaka as the experimental class implementing PBL and SDN Warungketan as the control class. The research instrument was a mathematical problem-solving test. The results showed that the application of the PBL model had a positive effect on students’ mathematical problem-solving abilities, with an average N-Gain of 0.59 in the experimental class and 0.39 in the control class, both in the medium category. Thus, the PBL model is effective in improving students’ mathematical problem-solving skills.